2019
DOI: 10.1038/s41598-018-37038-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of HLA-DR and Topoisomerase I Epitope Modulated Genetic Risk for Systemic Sclerosis

Abstract: The association of systemic sclerosis with anti-Topoisomerase 1 antibody (ATASSc) with specific alleles of human leukocyte antigen (HLA)-DR has been observed among various ethnics. The anti-Topoisomerase 1 antibody is a common autoantibody in SSc with diffuse cutaneous scleroderma, which is one of the clinical subtypes of SSc. On the other hand, an immunodominant peptide of topoisomerase 1 (Top1) self-protein (residues 349–368) was reported to have strong association with ATASSc. In this study, molecular dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Interesting, in previous investigations this specific allele has been associated with the development of atopic dermatitis in a small cohort of 185 children of Korean origin (13). The same allele has been associated with systemic sclerosis with anti-topoisomerase antibodies (14) or with the risk of developing systemic juvenile arthritis (15) or atopic dermatitis (13). The same Swiss group of Hasan Ali et al also demonstrated an association trend between HLA DBQ1 * 03:01 allele and the development of colitis.…”
Section: Patients At Risk But Without Previous Clinical Evidence Of Amentioning
confidence: 93%
“…Interesting, in previous investigations this specific allele has been associated with the development of atopic dermatitis in a small cohort of 185 children of Korean origin (13). The same allele has been associated with systemic sclerosis with anti-topoisomerase antibodies (14) or with the risk of developing systemic juvenile arthritis (15) or atopic dermatitis (13). The same Swiss group of Hasan Ali et al also demonstrated an association trend between HLA DBQ1 * 03:01 allele and the development of colitis.…”
Section: Patients At Risk But Without Previous Clinical Evidence Of Amentioning
confidence: 93%
“…Interestingly, the AA positions for HLA-DPB1 and HLA-DRB 1 overlap and all 8 AAs positions can be associated with four of five binding pockets described for class II HLA molecules 48 likely interfering with (auto-)antigen binding. In addition, three of the HLA-DRB1 AA positions (37, 58, and 74) are close to sites (30, 60, and 74) which have been described to play a role in binding the consensus antigenic peptide of the topoisomerase I epitope, auto-antibodies to which define the ATA + subgroup of SSc patients 49 . Furthermore, we found that the C4 -independent genetic association with SSc can be explained by 10 independent classical HLA-Alleles instead of AAs, seven of which overlap with a model of nine independent HLA-Alleles recently described 50 , which supports the independence of C4 and HLA associations with SSc.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings indicated that the binding affinity between the HLA-DQ molecule encoded by DQA1*05:03 and the immunodominant AQP4 peptide was relatively high, and that the energetic stability of the complex was also higher than that of other HLA-DQA1 alleles. In fact, the HLA-DR molecule encoded by the systemic sclerosis with anti-Topoisomerase 1 antibody (ATASSc)-associated alleles ( HLA-DRB1*08:02 , HLA-DRB1*11:01 and HLA-DRB1*11:04 ) or suspected allele ( HLA-DRB5*01:02 ) is reported to have a high binding affinity for the immunodominant peptide of topoisomerase 1 self-protein (residues 349–368) 30 . Furthermore, it has been shown that high stability of the peptide-MHC class II complex broadens the clonotypic repertoire of antigen-specific CD4+ T cells, while low stability skews it into a restricted repertoire with high affinity TCRs for pMHC 31 .…”
Section: Discussionmentioning
confidence: 99%